GEOECOLOGICAL CONSEQUENCES OF THE COMMUNAL ENTERPRISES WORK WITH IN WESTERN BUG RIVER BASIN - Койнова, І. Б. (Man and Environment. Issues of Neoecology)
In the article, current ecological state problems, which are caused by the communal enterprises work within river basins in Ukraine, were reviewed. The Western Bug River is a right tributary of the river Visla, which flows into the Baltic Sea, so the causes of a water quality decrease research has a cross-border value. Physical geography features of the Western Bug river basin, a volume of the water intake, a quantity and a quality of water which is returned after use, were described. Sources of the water pollution and the state of geocomponents of the river basin were found. The biggest water pollution sources among communal enterprises – Lviv communal pollution control facilities and Lviv city landfill were explored in detail. Based on the fund materials analysis and field research, an analysis of the quality indicators of the downstream water pollution changing was made. Geoecological consequences for a basin geosystem were characterized. Main problems were found and the ways of solution were identified: increasing environmental awareness, increase forest cover, observance of buffer strips along water bodies, reclamation of disturbed land area increase natural-reserve fund